Multi-criteria assessment of cropping systems for the sustainable intensification in the Pampas - Cano, Priscila (2023)
The transformation of cropping systems towards sustainable intensification (SI) is essential in order to meet the demands of society. In the Pampas region of Argentina, most agricultural research has focused on crop ecophysiology and agronomic factors, although what seems to be lacking is an integrated evaluation of cropping systems to determine their alignment with SI trends. Multi-criteria analysis (MCDA) methods provide a formal framework to assess trade-offs between production and sustainability, rendering them useful for SI analysis. This paper aims to compare and rank the cropping systems available in the rolling Pampas, the corn belt of Argentina, based on their alignment with SI trajectories, using the multi-criteria decision model “Preference Ranking Organization Methods for Enrichment Evaluations” (PROMETHEE).